2023
DOI: 10.1111/ene.16139
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cardiovascular health is associated with slower cognitive decline

Naomi Vidal Ferreira,
Natalia Gomes Gonçalves,
Claudia Szlejf
et al.

Abstract: BackgroundLife's Simple 7, a lifestyle and cardiovascular index associated with cognition, has been updated to Life's Essential 8 (LE8) to include sleep. LE8 has been related to cardiovascular outcomes but its association with cognition is unclear.MethodsIn this longitudinal analysis of the Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil), LE8 score was based on health behaviors (diet, physical activity, nicotine exposure, and sleep health) as well as health‐related factors (body mass index, blood li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…ECFC mitochondria in AD have not been investigated so far. As mentioned, CVRFs are affecting ECFCs and therefore, lower cardiovascular risk is associated with slower progression, i.e., cognitive decline, in the general population [280]. Due to the fact that CVRFs cause mitochondrial dysfunction in ECFCs, a link between mitochondrial dysfunction in ECFCs and AD, underlining the importance of future research in this field is suggested.…”
Section: Endothelial Progenitor Cells In Neurodegenerative Disordersmentioning
confidence: 99%
“…ECFC mitochondria in AD have not been investigated so far. As mentioned, CVRFs are affecting ECFCs and therefore, lower cardiovascular risk is associated with slower progression, i.e., cognitive decline, in the general population [280]. Due to the fact that CVRFs cause mitochondrial dysfunction in ECFCs, a link between mitochondrial dysfunction in ECFCs and AD, underlining the importance of future research in this field is suggested.…”
Section: Endothelial Progenitor Cells In Neurodegenerative Disordersmentioning
confidence: 99%